Integrated Genomic Analyses From Low-Depth Sequencing Help Resolve Phylogenetic Incongruence in the Bamboos (Poaceae: Bambusoideae) - Chalopin, Domitille; Clark, Lynn G.; Wysocki, William P.; Park, Minkyu; Duvall, Melvin R.; Bennetzen, Jeffrey L. (Frontiers in Plant Science, 2021)
The bamboos (Bambusoideae, Poaceae) comprise a major grass lineage with a complex evolutionary history involving ancient hybridization and allopolyploidy. About 1700 described species are classified into three tribes, Olyreae (herbaceous bamboos), Bambuseae (tropical woody bamboos) and Arundinarieae (temperate woody bamboos). Nuclear analyses strongly support monophyly of the woody tribes, whereas plastome analyses strongly support paraphyly, with Bambuseae sister to Olyreae. Our objectives were to clarify the origin(s) of the woody bamboo tribes and resolve the nuclear vs. plastid conflict using genomic tools. For the first time, plastid and nuclear genomic information from the same bamboo species were combined in a single study. We sampled 51 species of bamboos representing the three tribes, estimated their genome sizes and generated low-depth sample sequence data, from which plastomes were assembled and nuclear repeats were analyzed. The distribution of repeat families were found to agree with nuclear gene phylogenies, but also provide novel insights into nuclear evolutionary history. We infer two early, independent hybridization events, one between an Olyreae ancestor and a woody ancestor giving rise to the two Bambuseae lineages, and another between two woody ancestors giving rise to the Arundinarieae. Retention of the Olyreae plastome associated with differential dominance of nuclear genomes and subsequent diploidization in some lineages explains the paraphyly observed in plastome phylogenetic estimations. We confirm ancient hybridization and allopolyploidy in the origins of the extant woody bamboo lineages and propose biased fractionation and diploidization as important factors in their evolution.